Effects of hormonal contraceptives on serum glucose, lipid profile and some liver function test - Isam Hamo Mahmood; Israa Mohammid Jaber (University of Mosul, 2019)
Objective: To investigate the effects of  hormonal contraceptives on serum glucose, lipid profile and some liver function tests. Patients and Methods: One hundred and three women participated in this study. They were taken hormonal contraceptives including oral contraceptive pills  or injection for a period not less than 6 months up to 12 years . Another group consisting of one hundred non contraceptive users taken from the same population participated in the study as a control group. Blood samples were taken from the individual and sera were used for the determination of serum glucose, lipid profile and some liver function tests which include alkaline phosphatase (ALP), aspartate amino transaminase (AST) and alanine amino transaminase (ALT). Results: A highly significant values of serum glucose concentrations, total cholesterol, triglycerides and LDL- cholesterol were obtained in contraceptive users as compared with contraceptive non users. Whereas a non significant values of ALP, AST, ALT and HDL cholesterol were obtained. Conclusion: The use of hormonal contraceptives was associated with undesirable effects on serum glucose and lipid profile. Care should be taken when using hormonal contraceptives in women having diabetes mellitus or cardiovascular diseases. Key Words: Hormonal contraceptives, ALP, AST, ALT, lipid profile.